2020
DOI: 10.1007/s42770-019-00207-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and structural determinants on iron assimilation pathways in the plant pathogen Xanthomonas citri subsp. citri and Xanthomonas sp.

Abstract: Iron is a vital nutrient to bacteria, not only in the basal metabolism but also for virulent species in infection and pathogenicity at their hosts. Despite its relevance, the role of iron in Xanthomonas citri infection, the etiological agent of citrus canker disease, is poorly understood in contrast to other pathogens, including other members of the Xanthomonas genus. In this review, we present iron assimilation pathways in X. citri including the ones for siderophore production and siderophore-iron assimilatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 69 publications
(89 reference statements)
0
3
0
1
Order By: Relevance
“…Likewise, Fe 2+ transport by Feo can determine the outcomes of bacterial infections within animal and plant hosts in some pathogens ( 2 , 5 ). These include the human intestinal and gastric pathogens Salmonella enterica ( 6 ) and Helicobacter pylori ( 7 ) and plant pathogens such as Xanthomonas species ( 8 , 9 ). Despite its importance in bacterial iron acquisition, the evolution and working mechanism of the Feo system remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Fe 2+ transport by Feo can determine the outcomes of bacterial infections within animal and plant hosts in some pathogens ( 2 , 5 ). These include the human intestinal and gastric pathogens Salmonella enterica ( 6 ) and Helicobacter pylori ( 7 ) and plant pathogens such as Xanthomonas species ( 8 , 9 ). Despite its importance in bacterial iron acquisition, the evolution and working mechanism of the Feo system remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…The organization of these three bfeA -like genes upstream of xss is strikingly similar to what was observed in X. citri subsp. citri ( 62 ) and X. oryzae pv oryzae ( 42 ). Wang et al ( 42 ) named the genes bfeA , bfeA2 , and bfeA3 and reported that mutating bfeA alone ended up in a reduced-virulence phenotype in planta .…”
Section: Resultsmentioning
confidence: 99%
“…animalis, we identified several gene clusters that are highly characteristic of this organism, the most prominent of which encodes the high affinity ferrous iron transport system FeoA/B. Orthologs of the FeoAB transporter are crucial for virulence in a variety of organisms, including the oral pathobiont P. gingivalis (27,28) as well as other heavily studied animal and plant pathogens like Salmonella enterica, Helicobacter pylori, and Xanthomonas species (29)(30)(31)(32). It is conceivable that in addition to the core collection of irontransport genes encoded by oral fusobacteria (Table S8), the additional high affinity FeoAB iron transporter could provide a specific growth advantage to Fn.…”
Section: Discussionmentioning
confidence: 99%